Pencarian Jarak Terdekat Lokasi Rumah Makan Tradisional Kota Palangka Raya Dengan Menggunakan Algoritma Breadth First Search - Sitinjak, Maruli Valentino; Ronaldo, Deddy; Parhusip, Jadiaman (Journal of Information Technology and Computer Science, 2023)
In determining the location of the desired traditional restaurant, of course, consumers need information or criteria to choose the closest traditional restaurant according to their needs, while information about the location, menu list and condition of the food place is still limited. This can make some users choose the location of a restaurant that is far away because they do not have enough information about the location of the nearest restaurant. Based on these problems, a system that can provide information is needed and is facilitated by finding the nearest location for traditional restaurants. This study aims to build a geographic information system that displays information and the location of traditional restaurants presented in the form of digital maps. This research applies the Breadth First Search (BFS) algorithm by testing the Haversine formula method system for finding the nearest location, HereMaps as a digital map builder, and developed based on a website. Making this application using the waterfall method, at the analysis stage the analysis stage is carried out on the things needed for website creation. At the design stage, program modeling is described in the Unified Modeling Language (UML). Then at the coding stage of making this website using the Visual Studio Code (VSC) and xampp applications and testing this application using the black box method.